Effects of meal replacement therapy on body weight, glycemic control and cardiovascular disease risks in obese type 2 diabetes patients - Gew, Soon Peng (2018)
Obesity is a common presentation in patients with type 2 diabetes mellitus (T2DM). Reducing as little as 5% of body weight may assist in improving diabetes-related outcomes. While the use of meal replacement therapy (MRT) as part of the medical nutrition therapy (MNT) is recommended, its effectiveness remains unclear, especially in the Malaysian context. This study has evaluated the effect of MRT on body weight, glycemic control and cardiovascular disease (CVD) risks in obese patients with T2DM. Thirty-two (n = 32) obese participants with T2DM (mean; age = 46.4 ± 8.2 years old; female = 34.4%, body mass index (BMI) = 31.8 ± 4.9 kg/m2; glycated haemoglobin (HbA1c) = 8.8 ± 1.5%) were recruited from the National Diabetes Institute (NADI), Diabetes Resource Centre. Participants were randomised to either MRT (n = 16) or standard dietetic therapy (SDT) group (n = 16) for 12- weeks study. All of the participants received the MNT from a dietitian at Diabetes Resource Centre with iso-caloric prescriptions at 1200 kcal/day depending on their needs. Participants in the MRT group were asked to replace their two meals with the two meal replacements in a day, with a snack and healthy meal plan at dinner time. The SDT group was asked to consume three carbohydrate-controlled meal plan and a snack. The parameters of body weight, body composition, glycemic control and CVD risks were assessed at baseline, 6 and 12 weeks. The data presented based on intention-to-treat analysis. A total of 27 participants completed the study for an 84.4% response rate (MRT = 14, 87.5%; SDT = 13, 81.3%). The baseline characteristics were comparable between groups. At 12-weeks, the MRT group had a significantly large magnitude of changes (ηp2 = 0.272, p = 0.010) and greater reduction in body weight (83.3 ± 13.0 kg, Δ baseline = -3.5 ± 0.5 kg) than the SDT group (87.2 ± 20.8 kg, Δ baseline = -1.1 ± 2.4 kg; p < 0.01). The percentage of weight loss in the MRT group (Δ baseline = -4.1 ± 2.1%) was significantly greater than the SDT group (Δ baseline = -1.4 ± 2.5%; p < 0.01). Significant improvements in BMI and body fat percentage were also observed in the MRT group as compared to the SDT group (p < 0.01). In general, the differences between groups on HbA1c were not significant. However, the MRT group had a greater reduction in HbA1c and dosage of OAD as compared with the SDT group. HbA1c in the MRT group was reduced from 9.1 ± 1.5% to 7.9 ± 1.3% (Δ baseline = -1.1%; p < 0.01), which was not observed in the SDT group (baseline = 8.5 ± 1.5%; 12-weeks = 8.0 ± 1.1%; Δ baseline = -0.5%; p = 0.11). Fasting plasma glucose (FPG) also declined in the MRT group (Δ baseline = -1.2 ± 2.2 mmol/L; p < 0.05), but not in the SDT group, with no significant differences between groups. Interestingly, analysis of minimised confounders effects by removing the participants who had changed type of oral antidiabetic drug (OAD) showed significant differences, with a large magnitude of changes (ηp2 = 0.255, p = 0.006). Weight loss was associated with HbA1c reduction. CVD risks tended to improve more in the MRT group than in the SDT group, but no significant differences were found between the groups. 72.5% of the MRT participants adhered to the intervention. Adherence to MRT was associated with weight loss, visceral fat reduction, HbA1c reduction and high-sensitivity C-reactive protein (hs-CRP) reduction. Both interventions showed no changes in terms of safety parameters (liver and kidney function test) and no adverse reactions were found among obese participants with T2DM at 12-weeks. In conclusion, the MRT group have achieved a reduction of weight loss nearly 5% and HbA1c > 1% at 12 weeks. MRT group had greater weight loss, BMI and percentage of body fat than the SDT group at 12 weeks. The differences between groups on HbA1c were not significant. However, the observations were became significant, with a large magnitude of changes when minimising the confounder effect after excluding participants who changed type of OAD. Within the MRT group, improvements in glycemic control and CVD risks were evident, and were not observed within the SDT group. The MRT group had high adherence rate at 12 weeks. Both interventions were safe for obese participants with T2DM at 12 weeks. Further longer-term study is warranted.